Proses Pembelajaran Beladiri Kelas 8 di Kecamatan Jati Kabupaten Kudus - Thommah, Abdullah Fattakhu; Setiawan, Ipang (Indonesian Journal for Physical Education and Sport, 2023)
The research was conducted with the aim of knowing the lesson plans for teachers of Physical Education, Sports and Health for grade 8 junior high schools in Jati District. This research is in the form of a survey using a descriptive research approach, quantitative methods, and using an instrument in the form of a questionnaire. The subjects in this study were teachers and students of grade 8 junior high school in Jati Sebayak District, 7 teachers and 141 students. The results of the research show that teachers and students in learning self-defense materials for grade 8 junior high school in Jati District that teacher planning is included in the very high category at 43%, teacher implementation is included in the high category at 43%, teacher evaluation is included in the low category at 57%. The conclusion is that teacher planning in learning martial arts material for grade 8 junior high school in Jati District is included in the very high category, while planning is included in the high category, the teacher's implementation in learning martial arts material for grade 8 junior high school in Jati District is included in the high category, while student implementation is included in the category low, the evaluation of teachers in learning martial arts material is in the low category, researchers can only carry out PJOK learning research on martial arts materials, for further researchers it is recommended to use samples and other variables, so that it is hoped that the implementation of learning can be widely identified.